Climbing The Mountain : My Search for Meaning - Douglas, Kirk, 1916- (New York Simon & Schuster, 1997)
The story of how Kirk Douglas found new purpose to his life through Judaism, after sustaining crippling injuries in a helicopter crash in 1991. There is also an account of his recovery from a stroke that left him partially paralysed and unable to speak.
Include Epilogue, Index and Illustration
Keywords: Motion picture actors and actresses -- United States -- Douglas, Kirk, 1916-